Planning the Organization Activity in Economy of Knowledge - S. N. Kukushkin (Вестник Российского экономического университета имени Г. В. Плеханова, 2019)
The article studies one of the key business processes of the organization, i.e. planning. Planning cannot create added value (a product or service) for the customer, but it allows us to understand what values are required by the customer and to identify and distribute organization resources to meet their rising and changing needs. At the same time planning plays an important organizational role in the organization, as it coordinates the work of its structural bodies in order to attain the goals of the organization itself and its divisions. Planning gives flexibility to the organization in complicate changing conditions of its functioning and helps it to survive. The author points out that the important aspect of the planning process is raising personnel engagement and its motivation to reach organizational and group goals. At the same time planning should promote freedom of structural divisions of the organization. And finally, another important aspect of plan/forecast development is control over their execution.